Prospects of combined antihypertensive-psychocorrective therapy in women with arterial hypertension and anxiety-depressive disorders: clinical randomized placebo uncontrolled trial - V. V. Skibitskiy; Yu. E. Ginter; A. V. Fendrikova; D. V. Sirotenko (Кубанский научный медицинский вестник, 2021)
Background. Anxiety-depressive disorders (ADD) afflict almost half of patients with arterial hypertension (AH). AH aggravation by psychoemotional disorders causes a more severe illness and rapid target organ injury, particularly, the increased arterial stiffness and central aortic pressure (CAP). However, the prospects of combined antihypertensive-antidepressant treatments in AH-ADD patients remain largely unexplored.Objectives. The effect assessment in combined antihypertensive-psychocorrective therapy on circadian blood pressure (BP), vascular stiffness and CAP, anxiety and depression in women with AH and ADD.Methods. The study enrolled 60 AH-ADD women randomised between two cohorts. Cohort 1 received a fixed combination of valsartan and hydrochlorothiazide, bisoprolol and sertraline antidepressant; cohort 2 only had same combined AH therapy. Past 24 weeks of trial, all patients had a general clinical examination and daily blood pressure monitoring (DBPM) with BpLab Vasotens (Petr Telegin Ltd., Russia) and control of daily BP, CAP and vascular stiffness. The psychometric HADS and CES-D scales were used along with psychiatric counselling.Results. Past four weeks of treatment, the target blood pressure (TBP) was revealed in 60 and 36.7% patients, and in 90 and 66.6% — past eight weeks in cohorts 1 and 2, respectively. Cohort 1 vs. 2 required a lower valsartan dose to attain TBP. Past six months, both cohorts showed improved main DBPM values reflecting vascular stiffness and CAP. However, a statistical decrease in nocturnal central and peripheral BP, as well as improved BP variability and vascular stiffness were registered at antidepressant use. A normalised daily BP profile was significantly more frequent in cohort 1. In addition, sertraline had a significant ADD-reductive impact.Conclusion. An antidepressant-combined conventional AH therapy in AH-ADD women facilitated a faster TBP achievement at lower AH agent doses and the significantly improved DBPM (nocturnal specifically), arterial stiffness and CAP values. A sertraline treatment improved the psychoemotional patient state.